PENGARUH RISIKO LIKUIDITAS, RISIKO KREDIT DAN RISIKO OPERASIONAL TERHADAP KINERJA KEUANGAN BANK (Studi pada Bank Umum yang terdaftar di BEI 2015-2017) - Olivia Dhenok Arumsari, 15.05.51.0381; sudiyatno, Bambang (Students' Journal of Economic and Management, 2019)
Profitability in the company is a reflection of the financial performance of a company and will affect the decisions of investors who will invest their capital into the company. This study examines the effect of liquidity risk, credit risk and operational risk on financial performance of companies listed on the Indonesia Stock Exchange. The sampling method uses purpose sampling for banking companies listed on the Indonesia Stock Exchange with the period 2015-2017, which are 28 companies for 3 years to be 84 data. The influence between variables is explained using the method of multiple regression analysis. The results showed that the LDR did not significantly influence ROA in the banking companies listed on the IDX for the period 2015-2017. NPL does not significantly influence ROA for companies listed on the IDX for the period 2015-2017. BOPO has a negative and significant effect on ROA in banking companies listed on the IDX for the period 2015-2017.